(untitled) (CIPEEX, 2022)
SYSTEMIC ARTERIAL HYPERTENSION (SAH) IS DEFINED BY THE BRAZILIAN SOCIETY OF CARDIOLOGY AS A MULTIFACTORIAL CLINICAL CONDITION CHARACTERIZED BY ELEVATED AND SUSTAINED BLOOD PRESSURE LEVELS (BP GREATER THAN OR EQUAL TO 140X90MMHG). THE OBJECTIVE OF THIS STUDY WAS TO EVALUATE THE PREVALENCE OF SYSTEMIC ARTERIAL HYPERTENSION, CONSIDERING THE FOLLOWING VARIABLES: GENDER, SCHOOLING AND AGE IN QUILOMBOLA, INDIGENOUS, RIVERSIDE AND RURAL COMMUNITIES COMPARED TO THE NATIONAL PANORAMA. THIS WORK WAS CARRIED OUT THROUGH A DATABASE IN THE SCIELO, GOOGLE ACADEMIC AND LILACS, THROUGH SCIENTIFIC JOURNALS RELATED TO THE SUBJECT ADDRESSED, WITH THE FOLLOWING DESCRIPTORS: SYSTEMIC ARTERIAL HYPERTENSION, HYPERTENSION AND NORTH, HYPERTENSION AND NORTHEAST, HYPERTENSION AND CENTER- WEST, HYPERTENSION AND SOUTHEAST, HYPERTENSION AND SOUTH. THE TEXTS WERE ANALYZED IN A COMPLETE WAY, BEING SELECTED THOSE THAT CORRESPONDED TO THE TOPIC APPROACHED. IN GENERAL, THERE WAS A SLIGHT PREDOMINANCE IN FEMALE INDIVIDUALS, OVER 60 YEARS OLD AND NOT LITERATE. AND WHEN COMPARING THE PREVALENCE OF HYPERTENSION IN THESE GROUPS WITH THE STATES IN WHICH THEY ARE LOCATED, HIGHER VALUES €‹€‹ARE VERIFIED. WE CONCLUDE THAT LOWER SOCIAL STRATA SUCH AS THOSE ADDRESSED IN THE STUDY IN QUESTION ARE FACTORS THAT DIRECTLY INTERFERE IN THE HEALTH OF INDIVIDUALS.